Effects of sildenafil on lipid profile and glycemic control in patients with type 2 diabetes mellitus and metabolic syndrome - Al-biati, Haedar Abdulhafith; Ismail, Sajida Hussein; Sahib, Ahmed Salih; Kazaal, Faris Abdul Kareem; Al-Rubaie, Salim (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Insulin resistance impairs nitric oxide (NO) bioavailability; obesity promotes a state of metabolic syndrome and damages the vascular endothelium by altering lipid profile. Phosphodiesterase-5 (PDE-5) inhibitors restore NO signaling may improve metabolic parameters through a number of mechanisms. We hypothesized that daily administration of the PDE-5 inhibitor; sildenafil will improve fasting plasma glucose (FPG), triglyceride (TG) levels and body weight, in obese diabetic patients. Methods: Totally, 25 obese diabetic male patients with metabolic syndrome treated with sildenafil 25 mg daily for 3 months. Body weight, FPG levels, and lipid profile were determined monthly. Results: Treatment with sildenafil caused a reduction in fasting glucose levels, fasting TGs, cholesterol, low-density lipoprotein (LDL), very-LDL and increased high-density lipoprotein; body weight was significantly reduced. Conclusion: We have provided the first evidence that sildenafil therapy improve glycemic control, lipid profile and body mass index in diabetic patients with metabolic syndrome.